The Impact of Screen Time on Social Communication Skills in Children with Autism Spectrum Disorder: A Comprehensive Review - Mohapatra, Soubhagyalaxmi (Gayaku Publisher, 2024)
A neurological impairment in brain functioning causes autism spectrum disorder (ASD), which keeps a youngster from having a normal social life like his peers. It makes it difficult to engage and converse with other people. It should come as no surprise that children's concerningly high screen time exposure has raised even more concerns. The use of electronic equipment has two drawbacks. Notwithstanding their advantages, they pose a number of risks to kids' cerebral development. Prior research has examined the impact of unsupervised screen usage on young children's white matter development. In the development of brain functions, the white matter plays a significant role. A qualitative analysis of the body of research on screen time exposure and its impact on social communication abilities in kids with ASD is the goal of this thorough assessment.Research is increasingly raising concerns regarding the negative behaviour and enhanced poor communication skills of children’s use of screens